2021
DOI: 10.1136/jitc-2021-002392
|View full text |Cite
|
Sign up to set email alerts
|

Shared inflammatory pathways and therapeutic strategies in COVID-19 and cancer immunotherapy

Abstract: COVID-19, the syndrome caused by the infection with SARS-CoV-2 coronavirus, is characterized, in its severe form, by interstitial diffuse pneumonitis and acute respiratory distress syndrome (ARDS). ARDS and systemic manifestations of COVID-19 are mainly due to an exaggerated immune response triggered by the viral infection. Cytokine release syndrome (CRS), an inflammatory syndrome characterized by elevated levels of circulating cytokines, and endothelial dysfunction are systemic manifestations of COVID-19. CRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 153 publications
0
8
0
1
Order By: Relevance
“…Intriguingly, NK-cell dysfunction and T-cell exhaustion were reported in MPN patients even in the absence of treatment, potentially resulting in an impaired response to SARS-CoV-2 infection, whereas suppressive effects by ruxolitinib in NK-cells and T-cells, which were reported too, resulted in its use in several COVID-19 clinical trials [ 5 ]. Two systematic reviews and one meta-analysis confirmed the protective role of JAK inhibitors in reducing the risk of mortality in hospitalized patients with COVID-19 [ 6 , 7 ]. So far, and with results opposite to ours, there is only one published study on 21 patients with myeloproliferative neoplasms which has demonstrated polyfunctional T-cell responses with no detrimental effect exerted by ruxolitinib, and significant higher post-vaccine anti-S IgG and neutralizing antibody titers in myelofibrosis compared to patients with other MPN subsets, after a single dose of BNT162b2 mRNA vaccine [ 8 ].…”
mentioning
confidence: 99%
“…Intriguingly, NK-cell dysfunction and T-cell exhaustion were reported in MPN patients even in the absence of treatment, potentially resulting in an impaired response to SARS-CoV-2 infection, whereas suppressive effects by ruxolitinib in NK-cells and T-cells, which were reported too, resulted in its use in several COVID-19 clinical trials [ 5 ]. Two systematic reviews and one meta-analysis confirmed the protective role of JAK inhibitors in reducing the risk of mortality in hospitalized patients with COVID-19 [ 6 , 7 ]. So far, and with results opposite to ours, there is only one published study on 21 patients with myeloproliferative neoplasms which has demonstrated polyfunctional T-cell responses with no detrimental effect exerted by ruxolitinib, and significant higher post-vaccine anti-S IgG and neutralizing antibody titers in myelofibrosis compared to patients with other MPN subsets, after a single dose of BNT162b2 mRNA vaccine [ 8 ].…”
mentioning
confidence: 99%
“…Only genetic depletion of the IFNα/β receptor protected mice from death. In addition, other cytokines released by inflammatory monocytes, such as IL1β, IL-6 (also confirmed in COVID-19 patients recently [ 18 ]), and inducible nitric oxide synthase, appeared important.…”
Section: Introductionmentioning
confidence: 64%
“…This drug showed clinical status improvement, although it was not statistically significant, in a phase 3 trial in patients with cardiometabolic risk factors [ 63 ]. Finally, (3) ruxolitinib is a JAK inhibitor with a similar mechanism to baricitinib [ 64 ].…”
Section: Discussionmentioning
confidence: 99%